1990
DOI: 10.1524/ract.1990.49.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Thorium with Phosphoric Acid

Abstract: The behaviour of 227 Th in the two-phase system HDEHP-C 6 H 6 / H3PO4 -HCIO4 -LÍCIO4 (μ = 0.2), has been investigated as a function of the independent equilibrium parameters which define the system. The data have been interpreted in terms of the formation of phosphoric complexes in the aqueous phase of order I with respect to H3PO4 and charge z. The values obtained were 1 < / < 5 and ζ = -3,0,1,2. Stability constants were determined. The composition of the complexes is proposed on the basis of partial atomic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…According to Bäes and Mesmer [31], thorium(IV) hydrolysis becomes detectable between pH 2 and 3. Moreover, Elyahyaoui et al [32] observed that at trace levels, thorium hydrolysis seems to start at even lower pH (pH 1.2). Since the slope in the log-log plot is determined within the pH range 1.65-3.60, the possibility of p = 0 cannot be excluded.…”
Section: Variation Of the Thorium Sorption With Phmentioning
confidence: 99%
“…According to Bäes and Mesmer [31], thorium(IV) hydrolysis becomes detectable between pH 2 and 3. Moreover, Elyahyaoui et al [32] observed that at trace levels, thorium hydrolysis seems to start at even lower pH (pH 1.2). Since the slope in the log-log plot is determined within the pH range 1.65-3.60, the possibility of p = 0 cannot be excluded.…”
Section: Variation Of the Thorium Sorption With Phmentioning
confidence: 99%
“…However, it was found that in the initial period ( 24 h), phosphate ions complex onto the oxide surface in a 1:1 stoichiometry at a fairly rapid rate, and then, in an extended period ( 25 h), the alumina phase transforms into an aluminum phosphate precipitate at a very slow rate [14]. Additionally, it was found that in the pH range 1.7-2, 80% of the Th(IV) appears as Th(H 2 PO 4 ) 4 , at pH 3, and the anionic complex is predominant and incorporates 90% of the thorium at solution conditions C H 3 PO 4 7 × 10 −2 mol/L and C Th ≈ 3 × 10 −4 mol/L [10]. Therefore, a strong effect of phosphate on the extent of adsorption of Th(IV) onto alumina may be expected.…”
Section: Introductionmentioning
confidence: 97%
“…Elyahyaoui et al [10] observed thorium hydrolysis starting at pH 1.2 at trace levels. In general, several monodentate surface complexation reactions,…”
Section: Introductionmentioning
confidence: 99%
“…The organic phases were composed of diethyl ether solutions 0.34 M in acetic acid. 233 U and 228 Th tracers, available in 3 M nitric acid stock solutions, were purified from the daughter activities prior to use with a procedure described previously [19]. Aliquots with activity of 3 Bq were taken from these stock solutions for the extraction and electrodeposition experiments.…”
Section: Methodsmentioning
confidence: 99%